2005
DOI: 10.1308/1478708051865
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and therapeutic endoscopic retrograde cholangiopancreaticography after Billroth II gastrectomy – safe provision in a district general hospital

Abstract: Ann R Coll Surg Engl 2005; 87: 274-6 274Endoscopic retrograde cholangiopancreatography (ERCP) is widely used in the diagnosis and treatment of pancreaticbiliary disease.1 It is available in most acute hospitals in the UK. However, there are potential difficulties in carrying out this examination following a Billroth II gastrectomy and few centres have wide experience of ERCP in this situation. In this study, we have evaluated the results of ERCP in Billroth II gastrectomy patients treated in a district general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…In the hospitals participating in our study, the proportion of LCBDE for treatment of CBDS patients was 1.8À19% for each hospital (data not shown). However, patients with multiple stones, duodenal diverticulum, severe strictures or obstructions, and severe kyphosis will require surgical methods [11,17,[20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…In the hospitals participating in our study, the proportion of LCBDE for treatment of CBDS patients was 1.8À19% for each hospital (data not shown). However, patients with multiple stones, duodenal diverticulum, severe strictures or obstructions, and severe kyphosis will require surgical methods [11,17,[20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have shown that surgical treatment is associated with higher postoperative mortality, morbidity and a longer hospital stay than non-surgical drainages (24, 25). Endoscopic retrograde cholangiography (ERCP) is usually difficult in these patients because of a distorted bowel loop due to the Billroth II reconstruction or Rouxen-Y esophagojejunostomy (26, 27). Afferent loop perforation is a specific complication of ERCP in these patients and these patients have a mortality rate varying from 0.7-5% (27).…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic retrograde cholangiography (ERCP) is usually difficult in these patients because of a distorted bowel loop due to the Billroth II reconstruction or Rouxen-Y esophagojejunostomy (26, 27). Afferent loop perforation is a specific complication of ERCP in these patients and these patients have a mortality rate varying from 0.7-5% (27). Therefore, we use PTBD as an initial treatment for patients with malignant biliary obstruction caused by metastatic gastric cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In large case series, technical failures have been reported for Billroth II (13% to 48%), [1][2][3][4][5][6][7][8] Whipple (31% to 46%), 9,10 and Roux-en-Y (33% to 67%) 11,12 anatomy. The reported rate of perforation for ERCP in this setting is 0% to 18%, with a mortality of 0% to 3%.…”
mentioning
confidence: 99%
“…The reported rate of perforation for ERCP in this setting is 0% to 18%, with a mortality of 0% to 3%. [1][2][3][4][5][6][7][8][9][10][11][12] It is worth noting that these studies were generally conducted at expert centers by endoscopists with a special interest in surgically altered anatomy. As a result of this ERCP experience, surgically altered anatomy may be considered a relative contraindication to EUS by some physicians.…”
mentioning
confidence: 99%